Methodological issues in religious studies with special attention to Lauri Honko's theoretical contribution - Kamppinen, Matti, 1961- (Lewiston : Edwin Mellen Press, 2011)
This book elucidates the conceptual or theoretical issues in religious studies by means of utilizing the tools of philosophical analysis. The academic discipline of religious studies is rich in conceptual systems that derive from ethnography, history, psychology, sociology and media studies. In line with other fields of research in cultural studies, religious studies adopt various theoretical resources in eclectic ways, and by the same token, imports various numerous conceptual issues from these adjacent fields. In addition to the rich conceptual systems within religious studies, the disciplin.
Title Page; Copyright Page; Blank Page; Blank Page; Table of Contents; Introduction; Chapter One; Chapter Two; Chapter Three; Chapter Four; Chapter Five; Chapter Six; Bibliography; Index
Description based upon print version of record.
Keywords: Anthropology of religion; Honko, Lauri; Religion -- Methodology; Religion; RELIGION / Education; Religion -- Methodology; Anthropology of religion; Honko, Lauri; Electronic books